2014
DOI: 10.2147/ijn.s75074
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic single-walled carbon nanotubes as efficient drug delivery nanocarriers in breast cancer murine model: noninvasive monitoring using diffusion-weighted magnetic resonance imaging as sensitive imaging biomarker

Abstract: Purpose Targeting doxorubicin (DOX) by means of single-walled carbon nanotube (SWCNT) nanocarriers may help improve the clinical utility of this highly active therapeutic agent. Active targeting of SWCNTs using tumor-specific antibody and magnetic attraction by tagging the nanotubes with iron oxide nanoparticles can potentially reduce the unnecessary side effects and provide enhanced theranostics. In the current study, the in vitro and in vivo efficacy of DOX-loaded SWCNTs as theranostic nanoprobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 26 publications
0
45
0
1
Order By: Relevance
“…Over the past decades, several nano-sized DDSs have been developed and applied by targeted drug delivery to cancer cells, such as liposomes, [4][5][6][7] polymeric micelles, [8][9][10][11] dendrimers, [12][13][14][15][16] carbon nanotubes, [17][18][19][20][21][22] inorganic nanoparticles, [23][24][25][26] and silica-based materials. [27][28][29][30][31] Among them, mesoporous silica nanoparticles (MSNs) have attracted much attention due to their unique physiochemical properties, such as large specific surface area and pore volume, controllable particle size, remarkable stability and biocompatibility, and high drug-loading capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, several nano-sized DDSs have been developed and applied by targeted drug delivery to cancer cells, such as liposomes, [4][5][6][7] polymeric micelles, [8][9][10][11] dendrimers, [12][13][14][15][16] carbon nanotubes, [17][18][19][20][21][22] inorganic nanoparticles, [23][24][25][26] and silica-based materials. [27][28][29][30][31] Among them, mesoporous silica nanoparticles (MSNs) have attracted much attention due to their unique physiochemical properties, such as large specific surface area and pore volume, controllable particle size, remarkable stability and biocompatibility, and high drug-loading capacity.…”
Section: Introductionmentioning
confidence: 99%
“…This would allow for reducing the drugs dosage, their concentrations on sites that are not of interest, and the side effects associated with chemotherapy and hormonal therapy [15,16]. In this regard, carbon nanomaterials with potential uses for the administration of drugs against cancer and breast cancer are being analyzed [17,22,23,[29][30][31]; they are considered as advantageous systems to control drug release in the organism and increase the efficiency of treatments and reduce their toxicity [17,32,33]. However, carbon nanomaterials have some disadvantages including their lack of solubility and low reproduction rate through their chemical functionalization and structural characterization.…”
Section: Drug Releasementioning
confidence: 99%
“…Recent studies in nanomedicine concluded that fullerenes, CNTs, and graphene have favorable properties for the carriage, targeted, and controlled delivery of chemotherapeutical drugs including taxol (paclitaxel), docetaxel (DTX), doxorubicin (DOX), and others [22,29,31,32,44,[50][51][52][53]. Raza et al [22] reported that the system conformed by the fullerene C 60 and DTX (C 60 /DXT) is able to improve up to 4.2 times the bioavailability of DTX and decreases the clearance of DTX by 50%.…”
Section: Drug Releasementioning
confidence: 99%
“…Pure MWCNTs are diamagnetic [24] and their magnetic steerability must be achieved by combining with ferro-or superparamagnetic components [25][26][27], for example, by decoration with Fe 3 O 4 [28] or Fe encapsulation (at the stage of c-CVD synthesis or via capillary forces as a posttreatment) [29]. Indeed, as c-CVD is a convenient and tunable one-step synthesis of Fe@MWCNTs, we decided to focus on effective loading of Fe@MWCNTs with chemotherapeutics representing various mechanisms of cytotoxicity and to anchor the drugs using different chemical routes.…”
Section: Introductionmentioning
confidence: 99%